Achievements and pending tasks in the development of the Mexican journal of biomedical engineering. - SOMIB, SOMIB (Revista Mexicana de Ingenieria Biomedica, 1991)
Achievements and pending tasks in the development of the Mexican journal of biomedical engineering.